The role of motivation in the development of the idea of pedagogical mutual relations of participants of educational process in higher education. - Gonchar E.V (Kharkov National Pedagogical University, 2010)
The essence of specific motivation, mechanism and its particular structure formation through the prism of the basic pedagogical categories of mutual relations of educational process agents are exposed. It is also proved that the functional characteristic of the motif gives a teacher the possibility of selecting the most witty arguments both to motivate the purpose of the activity, and to predict the thoughts, feelings and actions of students, effectively organize pedagogical mutual relations of educational process subjects.